Narratives of Women Offenders: Difficult Paths to Prison - Gaičevskytė-Savickė, Rimantė (Kriminologijos studijos, 2024)
Life-course criminology endeavors to comprehend the intricate interplay between individual traits, societal surroundings, and life occurrences that shape patterns of criminal behavior. Within this framework, the concept of life trajectories leading to criminality has emerged, underscoring the importance of scrutinizing women‘s narratives. This entails examining their childhood experiences, and adult challenges, and identifying circumstances that foster recidivism. The present publication unveils condensed accounts of female inmates at Panevėžys (Lithuania) women‘s prison, categorized into four trajectories: the typical woman or random offender, the victimized woman, the chronic offender, and the woman belonging to a marginalized cohort.
Keywords: life-course criminology; female offender; Lithuanian female pathways to crime